A new analysis of galaxy 2-point functions in the BOSS survey, including full-shape information and post-reconstruction BAO. Issue 2 (3rd February 2022) - Chen, Shi-Fan; Vlah, Zvonimir; White, Martin
Abstract: We present a new method for consistent, joint analysis of the pre- and post-reconstruction galaxy two-point functions of the BOSS survey. The post-reconstruction correlation function is used to accurately measure the distance-redshift relation and expansion history, while the pre-reconstruction power spectrum multipoles constrain the broad-band shape and the rate-of-growth of large-scale structure. Our technique uses Lagrangian perturbation theory to self-consistently work at the level of two-point functions, i.e. directly with the measured data, without approximating the constraints with summary statistics normalized by the drag scale. Combining galaxies across the full redshift range and both hemispheres we constrain Ωm = 0.303 ± 0.0082, H 0 = 69.23 ± 0.77 and σ8 = 0.733 ± 0.047 within the context of ΛCDM. These constraints are consistent both with the Planck primary CMB anisotropy data and recent cosmic shear surveys.